Improving Cadence and Walking Speed after Extracorporeal Shockwave Therapy: Preexperimental Study in Knee Osteoarthritis Patients - Amandha Boy Timor Randita; Imam Subadi; Nurul Kusuma Wardani; Ardhi Wicaksono Santoso; Soenarnatalina Melaniani (Wolters Kluwer - Medknow Publications, 2023)
Introduction: Current treatment for knee osteoarthritis (KOA) has aimed at inhibiting the degenerative processes of osteoarthritis by regenerative medicine. One of the physical modalities that have a regenerative effect is extracorporeal shockwave therapy (ESWT). There was limited evidence based for evaluating the improvement function of KOA, especially after ESWT management. This study aimed to investigate the effect of ESWT by serial evaluation of cadence and gait speed for patients with KOA. Methods: Preexperimental with one group design was conducted in this study. We recruited 14 participants diagnosed with KOA with scoring Kellgren-Lawrence Grades 2 and 3. ESWT piezo shockwave was applied once a week for 6 weeks. Evaluations of cadence and walking speed were conducted three times (pretest, mid-test at 3 weeks after therapy, and posttest at 1 week after the last session). Results: There was a significant improvement of cadence and gait speed pretest compared to mid-test (P = 0.004; P = 0.003) and posttest (P = 0.001; P = 0.001). However, there was no significant difference between mid-test and posttest results. Conclusions: Cadence and gait speed were improved significantly after ESWT treatment for KOA, especially after 3 weeks.